Improving Cell Recovery: Freezing and Thawing Optimization of Induced Pluripotent Stem Cells - Markus Uhrig; EZQUER, EDUARDO FERNANDO; EZQUER, EDUARDO MARCELO (My University, 2022)
Achieving good cell recovery after cryopreservation is an essential process when working with induced pluripotent stem cells (iPSC). Optimized freezing and thawing methods are required for good cell attachment and survival. In this review, we concentrate on these two aspects, freezing and thawing, but also discuss further factors influencing cell recovery such as cell storage and transport. Whenever a problem occurs during the thawing process of iPSC, it is initially not clear what it is caused by, because there are many factors involved that can contribute to insufficient cell recovery. Thawing problems can usually be solved more quickly when a certain order of steps to be taken is followed. Under optimized conditions, iPSC should be ready for further experiments approximately 4–7 days after thawing and seeding. However, if the freezing and thawing protocols are not optimized, this time can increase up to 2–3 weeks, complicating any further experiments. Here, we suggest optimization steps and troubleshooting options for the freezing, thawing, and seeding of iPSC on feeder-free, Matrigel™-coated, cell culture plates whenever iPSC cannot be recovered in sufficient quality. This review applies to two-dimensional (2D) monolayer cell culture and to iPSC, passaged, frozen, and thawed as cell aggregates (clumps). Furthermore, we discuss usually less well-described factors such as the cell growth phase before freezing and the prevention of osmotic shock during thawing.
Keywords: induced pluripotent stem cells; logarithmic cell growth phase; freezing protocol; thawing protocol; post-thaw cell recovery; ipsc storage and transport; preventing osmotic shock; cell aggregates; cell seeding density; cell culture techniques; cryopreservation; feeder cells; freezing; induced pluripotent stem cells; 4 (1 aminoethyl) n (4 pyridyl)cyclohexanecarboxamide; acetamide; actin; antioxidant; ascorbic acid; bicarbonate; calcium ion; catalase; collagenase; cryoprotective agent; cyclic gmp; deoxyribonuclease; dimethyl sulfoxide; edetic acid; ethylene glycol; fibroblast growth factor 2; glycerol; glycoprotein; glycosaminoglycan; ice; insulin; liquid nitrogen; magnesium ion; matrigel; methanol; phosphate buffered saline; polystyrene; propylene glycol; protein nodal; rho kinase inhibitor; selenium; sucrose; transferrin; transforming growth factor beta1; trypsin; uvomorulin; water; cell adhesion; cell aggregation; cell counting; cell junction; cell membrane; cell survival; cell viability; cryopreservation; crystal; crystallization; cytotoxicity; dehydration; fetal bovine serum; freeze thawing; freezing; glass transition temperature; human embryonic stem cell; incubation time; induced pluripotent stem cell; microbial contamination; microscopy; monolayer culture; mouth cavity; mycoplasma; nonhuman; oocyte; osmolality; osmotic stress; quality control; review; spermatozoon; systematic review; thawing; two dimensional cell culture; viscosity; vitrification; cell culture technique; feeder cell; freezing